2020
DOI: 10.3390/ijms21228451
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sodium Butyrate on Adventitious Shoot Formation Varies among the Plant Species and the Explant Types

Abstract: Histone acetylation plays an important role in plant growth and development. Here, we investigated the effect of sodium butyrate (NaB), a histone deacetylase inhibitor, on adventitious shoot formation from protoplast-derived calli and cotyledon explants of tobacco (Nicotiana benthamiana) and tomato (Solanum lycopersicum). The frequency of adventitious shoot formation from protoplast-derived calli was higher in shoot induction medium (SIM) containing NaB than in the control. However, the frequency of adventitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 61 publications
(79 reference statements)
1
10
0
Order By: Relevance
“…To investigate whether the enhancement of regeneration by 4PBA might be due to its HDAC inhibitor activity, in addition to its auxin activity, we performed western blot analyses to check histone acetylation levels in 4PBAtreated Arabidopsis seedlings. As previously reported in other research performed in Arabidopsis and Brassica napus (Lee et al 2020;Li et al 2014;Menge et al 2017), both TSA-treated and BUA-treated Arabidopsis seedlings exhibited increases for all types of histone acetylation we examined, i.e., H3K9Ac, H3K14Ac, H3K23Ac, H3K27Ac and H4Acs (detected H4K5Ac, K8Ac, K12Ac and K16Ac), compared to mock-treated tissues (Figure 2). In contrast, we found that histone acetylation levels of 4PBA-treated Arabidopsis seedling are indistinguishable from mock-treated tissue.…”
Section: Pba Does Not Enhance Histone H3 and H4 Acetylation At Least ...supporting
confidence: 86%
See 1 more Smart Citation
“…To investigate whether the enhancement of regeneration by 4PBA might be due to its HDAC inhibitor activity, in addition to its auxin activity, we performed western blot analyses to check histone acetylation levels in 4PBAtreated Arabidopsis seedlings. As previously reported in other research performed in Arabidopsis and Brassica napus (Lee et al 2020;Li et al 2014;Menge et al 2017), both TSA-treated and BUA-treated Arabidopsis seedlings exhibited increases for all types of histone acetylation we examined, i.e., H3K9Ac, H3K14Ac, H3K23Ac, H3K27Ac and H4Acs (detected H4K5Ac, K8Ac, K12Ac and K16Ac), compared to mock-treated tissues (Figure 2). In contrast, we found that histone acetylation levels of 4PBA-treated Arabidopsis seedling are indistinguishable from mock-treated tissue.…”
Section: Pba Does Not Enhance Histone H3 and H4 Acetylation At Least ...supporting
confidence: 86%
“…Indeed, both auxin treatment and wounding stress alter histone modifications, including histone acetylation, which positively regulates the expression of cellular reprogramming-related genes Yamamuro et al 2016). Trichostatin A (TSA) and butyric acid (BUA), well-known inhibitors of histone deacetylases (HDACs) that increase the level of acetylated histones, can be added during tissue culture to enhance plant tissue regeneration (Bie et al 2020;Lee et al 2020;Li et al 2014;Wójcikowska et al 2018). TSA treatment additionally alters auxin responsiveness (Li et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, TSA promoted the formation of callus and embryo-like structures from leaf explants of Arabidopsis [47,48]. We have already reported that the effect of sodium butyrate, one of HDAC inhibitors, on in vitro adventitious shoot formation is different for each plant species or for each type of plant tissue [49]. In this study, we reported that TSA treatment is able to increase the genome editing efficiency using lettuce and tobacco protoplasts.…”
Section: Discussionmentioning
confidence: 75%
“…To examine the relative expression level of the phytohormone-related genes as well as cell wall extension such as those encoding gibberellin (GA20ox-1), ethylene (ACO1), cytokinin (SICKX1), expansin ( EXP9 , EXP18 ), and auxin ( SIAA1 , SIAA3 ) after exposure of the plants to the VOCs, primers were designed according to the study of Tahir et al (2017) . Actin4 ( ACT4 ) was used as an internal control ( Lee et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%